Squamous cell carcinoma; a rare complication of long-standing renal stones. Case report and an overview - Shah, Hamad Ali; Khan, Asaf Alam; Hussain, Syed Munim; Muhammad Arsalan Ali (Journal of the Pakistan Medical Association, 2025)
Renal squamous cell carcinoma is an exceedingly rare and infrequent diagnosis, usually not suspected due to its rarity and non-specific radiological and clinical features. Patients are usually diagnosed at a late stage, with subsequent mortality. Surgical excision, usually a radical nephrectomy, remains the treatment of choice. We report a case of a 48-year-old female, presenting with generalised lower abdominal pain, who underwent a simple nephrectomy for a non-functioning kidney and was diagnosed as squamous cell carcinoma on a postoperative biopsy. Keywords: Renal Calculi, Hydronephrosis, Carcinoma, Squamous Cell Carcinoma.